Acute inhalant intoxication and delirium: a case report - Ateş, M. A.; Semiz, Ü. B.; Algül, A.; Başoğlu, C.; Ebrinç, S.; Çetin, M. (Journal of Dependence, 2008)
Thinner is a neurotoxic mixture widely used as an industrial solvent and contains 60-70% toluene. This substance has been shown to cause functional and structural changes in the central nervous system. Here, we present the case of a 55-year-old man who unknowingly ingested thinner orally and subsequently developed delirium. It is stated that approximately 5-10 ml of thinner orally is sufficient to cause serious complications.